Biochemical and endocrine responses to impact and collision during elite rugby league match play - McLellan, C. P.; Lovell, D. I.; Gass, G. C. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to investigate the relationship between the prematch and short-term postmatch biochemical and endocrine responses to the intensity, number, and distribution of impacts associated with collisions during elite Rugby League match play. Seventeen elite male Rugby League players each provided blood and saliva samples 24 hours prematch, 30 minutes prematch, 30 minutes postmatch, and then at 24-hour intervals for a period of 5 days postmatch to determine plasma creatine kinase concentration ([CK]) and salivary cortisol concentration ([sCort]). The intensity, number, and distribution of impact forces experienced by players during match play were recorded using portable global positioning systems (GPSs). The change in the dependent variables at each sample collection time was compared to 24 hours prematch and 30-minute prematch measures. The [CK] and [sCort] increased significantly (p < 0.05) during match play. Significant correlations (p < 0.05) were observed between the number of hit-ups and peak [CK] 24 hours postmatch, 48 hours postmatch, and 72 hours postmatch (p < 0.05). The number of impacts recorded in zone 5 (8.1-10.0G) and zone 6 (>10.1G) during match play was significantly correlated (p < 0.05) to [CK] 30 minutes postmatch, 24 hours post, 48 hours post, and 72 hours postmatch. The GPS was able to provide data on the intensity, number, and distribution of impacts resulting from collisions during match play. Elite Rugby League match play resulted in significant skeletal muscle damage and was highly dependent on the number of heavy collisions >8.1G. [CK] remained elevated 120 hours postmatch identifying that at least 5 days modified activity is required to achieve full recovery after elite Rugby League match play.